IDNLearn.com is designed to help you find reliable answers to any question you have. Join our platform to receive prompt and accurate responses from experienced professionals in various fields.

The quadratic function [tex]f(x)[/tex] has roots of -2 and 6, and it passes through the point [tex](1, 15)[/tex]. What is the vertex form of the equation of [tex]f(x)[/tex]?

A. [tex]f(x) = (x - 2)^2 + 16[/tex]
B. [tex]f(x) = (x + 2)^2 + 16[/tex]
C. [tex]f(x) = -(x - 2)^2 + 16[/tex]
D. [tex]f(x) = -(x + 2)^2 + 16[/tex]


Sagot :

To find the vertex form of the quadratic function \( f(x) \) that has roots -2 and 6 and passes through the point (1, 15), we follow these steps:

1. Start with the factored form of the quadratic equation:
Since the quadratic function needs to have roots at -2 and 6, it can be written in factored form as:
[tex]\[ f(x) = a(x + 2)(x - 6) \][/tex]
Here, \(a\) is a constant that we need to determine.

2. Use the point (1, 15) to solve for \(a\):
The function passes through the point (1, 15), which means when \(x = 1\), \(f(x) = 15\). Substitute \(x = 1\) and \(f(x) = 15\) into the equation:
[tex]\[ 15 = a(1 + 2)(1 - 6) \][/tex]
Simplify inside the parentheses:
[tex]\[ 15 = a(3)(-5) \][/tex]
[tex]\[ 15 = a \cdot -15 \][/tex]
Solve for \(a\):
[tex]\[ 15 = -15a \][/tex]
[tex]\[ a = -1 \][/tex]

3. Write the quadratic function with the determined \(a\) value:
Now we know that \(a = -1\), so:
[tex]\[ f(x) = -1(x + 2)(x - 6) \][/tex]

4. Expand the function to convert it to standard form:
Expand the product:
[tex]\[ f(x) = -1(x^2 - 4x - 12) \][/tex]
Distribute \(-1\):
[tex]\[ f(x) = -x^2 + 4x + 12 \][/tex]

5. Convert the function to vertex form:
To convert \(f(x) = -x^2 + 4x + 12\) to vertex form, we complete the square.

- First, factor out \(-1\) from the quadratic and linear terms:
[tex]\[ f(x) = -(x^2 - 4x) + 12 \][/tex]

- To complete the square inside the parentheses, add and subtract \(\left(\frac{4}{2}\right)^2 = 4\):
[tex]\[ f(x) = -(x^2 - 4x + 4 - 4) + 12 \][/tex]
[tex]\[ f(x) = -((x^2 - 4x + 4) - 4) + 12 \][/tex]
[tex]\[ f(x) = -((x - 2)^2 - 4) + 12 \][/tex]

- Simplify by distributing the \(-1\):
[tex]\[ f(x) = -(x - 2)^2 + 4 + 12 \][/tex]
[tex]\[ f(x) = -(x - 2)^2 + 16 \][/tex]

So, the vertex form of the quadratic equation is:
[tex]\[ f(x) = -(x - 2)^2 + 16 \][/tex]

Therefore, the correct choice is:
[tex]\[ f(x) = -(x - 2)^2 + 16 \][/tex]